Lecturers’ Perception of Moodle-based LMS in Speaking Class - Bramy Biantoro; Rosalin Ismayoeng Gusdian (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
Background: Many Indonesian universities use Moodle-based LMS as suggested by the Ministry of Education. The study aimed at examining English Speaking course lecturers’ perception of Moodle-based LMS. Two important questions to dig out lecturers’ perceptions included supporting features in Moodle LMS preferred by lecturers in Speaking courses and how they perceive Moodle as the main LMS for Speaking courses. Methodology: Qualitative descriptive was utilized. Three Speaking course lecturers of English Language Education Department were selected based on some criteria. Semi-structured interviews were used to collect the data. The interview questions covered benefits of Moodle-based LMS in speaking class, support of LMS in learning speaking and learning autonomy, and possible problems during the use of LMS. The data were then transcribed into textual forms and analyzed narratively. Findings: Several menus preferred by lecturers were assignment, page, and quiz. There were also less preferred menus on Moodle, including video conference, attendance, and writing-oriented activities (i.e., chat and forum) menus. It is also found that participants held both positive and negative views towards Moodle. Conclusion: Major findings of the study suggest that Moodle offered a number of menus that were considered beneficial for the participants in conducting their classes. Generally, they also held positive perceptions towards the LMS and suggest some room for improvement for the LMS. Originality: Little attention has been paid to Moodle-based LMS is carried out and the lecturers’ perception on its implementation in the speaking classes. Thus, the current study is deemed necessary.